2021
DOI: 10.1002/ppap.202100152
|View full text |Cite
|
Sign up to set email alerts
|

Entering the plasma agriculture field: An attempt to standardize protocols for plasma treatment of seeds

Abstract: Plasma treatments are currently being assessed as a seed processing technology for agricultural purposes. There is sufficient information as a proof-of-concept, but a lack of standardization in the methodology prevents a convincing evaluation of plasma treatment on seeds. It would be helpful to coordinate research efforts to make the entry for newcomers into this interdisciplinary field less overwhelming and to aid in transferring this technology into the industry by establishing a common protocol. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 134 publications
(799 reference statements)
0
15
0
Order By: Relevance
“…Typical discharges differ in electrode arrangement, power sources, gas pressure, and include glow discharge, plasma jets, low-pressure capacitively coupled plasma (CP) discharge, corona discharge, dielectric barrier discharge (DBD), diffuse coplanar surface barrier discharge (DCSBD), etc. (for details, see reviews [ 19 , 22 , 27 , 28 , 29 , 30 ]). In this review, the common abbreviation NTP is used for plasma generated by all types of devices.…”
Section: Definitions Of Plasma Low-temperature Plasma and Description...mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical discharges differ in electrode arrangement, power sources, gas pressure, and include glow discharge, plasma jets, low-pressure capacitively coupled plasma (CP) discharge, corona discharge, dielectric barrier discharge (DBD), diffuse coplanar surface barrier discharge (DCSBD), etc. (for details, see reviews [ 19 , 22 , 27 , 28 , 29 , 30 ]). In this review, the common abbreviation NTP is used for plasma generated by all types of devices.…”
Section: Definitions Of Plasma Low-temperature Plasma and Description...mentioning
confidence: 99%
“…NTP does not cause thermal damage to heat-sensitive biological systems such as living cells and tissues. Therefore, this technology has many applications in biomedical technologies [ 8 , 9 , 10 , 11 , 12 ], for o has shown potential to improve agronomic seed quality by surface decontamination, germination enhancement, and promotion of plant growth, as discussed in numerous reviews published recently [ 3 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Intensive research is currently being conducted on the application of NTP in agriculture, forestry, and food industries in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not only is the substrate different, seedling instead of seed, but the chemistry could also be different. Nevertheless, it is encouraging to see significant overlap between these studies because this promises some robustness in the experimental results, and this might be explained by using the same seed type, similar operating parameters for the plasma-seed treatment, and extraction time point [ 6 ]. The RNA extraction was performed 48 h after plasma treatment on 4-day-old seedlings, so, both studies extracted from 6-day-old seedlings, and the main difference was that plasma treatment was performed on either the seed or seedling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that seed germination can be accelerated, or the plant properties can be altered where root length, shoot length, harvest mass or stress and disease resistance have increased after plasma treatment [ 4 , 5 ]. Despite the numerous successful results obtained in other studies, it remains elusive which plasma treatment parameters are required to affect plant growth parameters mainly because of the plethora of physical, chemical, and biological variables [ 6 ]. Therefore, the focus has recently shifted toward analyzing the gene transcription in seedlings and plants developing from plasma-treated seeds or even analyzing the methylation on genes or proteins using quantitative PCR (qPCR) or other high throughput methods, respectively [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first applications of cold plasmas was the treatments of conventional seeds [ 39 , 40 ]. This includes various applications in seed treatment with several purposes [ 41 , 42 , 43 ]. Many authors have shown that plasma treatments can increase seed germination and speed up the whole process of plantlet development [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%